Analysis of Balagah on the surah At-Tholaq and his Meaning and his Application in Learning material Of Balagah Science At Mahad Tarbiyatul Mu’allimin Alhalimy Foundation Sesela - Safarudin; Abdul Azis (Cordova Journal : languages and culture studies, 2022)
Balagah science has a strong relationship with the al-Qur’an so that the main goal in leraning Balagah science aording to muslims is to be able to understanding the meaning the Qur’ani Texts and their meanings. Understand the meaning Of the Qur’an not only from Its real Lafaz where the sentences are composed , but also from their inner ues. Also Balagah Science learning has not ean focused on forming student abilities in analizing the meaning of the Qur’an from the point of view of Balagah Science, this is because at least is uses examples of epressions quoted from the Qur’an . This Study uses a descriptive qualitative research. This study has two objectives. The first Objetive is to reveal the Balagah Tehnique in the Surah At-Tholaq and His Meanings, The Second Objetive is to strengthen these techniques in learning Balagah At Mahad Tarbiayul Mu’allimin Al Halimy Foundation sesela, based on the result of the research process corried out by research , it is conluded that, in the surah At-Tholaq there are several Balagiyah Techniques, including: 1) Majaz Mursal, 2) Isti’arah, 3) Ithnab, 4) Qoshor, 5) khobar and Insya’ , 6) Husnu Ta’lil. As for the procedure for Implementing these Balagiyah Techniques the qiasyah Method is Used , in which learning egins with Qawa’id Balagiyah in general and then brings in examples quoted from surah At-Tholaq as a comprasion from the Qowa’id and as reinforcement for student Understanding.